ENDOCRINOLOGY IN THE TIME OF COVID-19: Management of calcium metabolic disorders and osteoporosis. Issue 2 (August 2020) - Gittoes, Neil J; Criseno, Sherwin; Appelman-Dijkstra, Natasha M; Bollerslev, Jens; Canalis, Ernesto; Rejnmark, Lars; Hassan-Smith, Zaki
Abstract : Endocrinologists have had to make rapid changes to services so that resources can be focused on the COVID-19 response to help prevent spread of the virus. Herein we provide pragmatic advice on the management of commonly encountered calcium metabolic problems and osteoporosis. Non-urgent elective appointments should be postponed, and remote consultations and digital health solutions promoted. Patients should be empowered to self-manage their conditions safely. Patients, their caregivers and healthcare providers should be directed to assured national or international online resources and specific patient groups. For patients in acute hospital settings, existing emergency guidance on the management of hyper- and hypo-calcaemia should be followed. An approach to osteoporosis management is outlined. IV zoledronic acid infusions can be delayed for 6–9 months during the pandemic. Patients established on denosumab, teriparatide and abaloparatide should continue planned therapy. In the event of supply issues with teriparatide or abaloparatide, pausing this treatment in the short term is likely to be relatively harmless, whereas delaying denosumab may cause an immediate increased risk of fracture. The challenge of this pandemic will act as a catalyst to innovate within our management of metabolic bone and mineral disorders to ensure best use of resources and resilience of healthcare systems in its aftermath.